Identifying Friction between Large-scale Agile Software Development and Plan-based Business Processes - Ingmarsson, Robin; Altehed, Tobias (My University, 2011)
This Master of Science Thesis is reported here in a hybrid format, i.e. the main content of the Work is reported as a scientific article conforming to the Empirical Software Engineering Journal’s template, complemented by additional appendices relevant for the examination at Chalmers University of Technology.
Keywords: Information Technology; Informationsteknik